The tendency to arrest victims of domestic violence: a preliminary analysis of officer characteristics - Saunders, Daniel G. (Journal of interpersonal violence, 1995)
The arrest of victims of domestic violence occurs at an unexpectedly high rate and is a problem of growing concern. In this study of 111 police officers, it was predicted that those inclined to arrest the victim would have more negative stereotypes and attitudes toward victims and women in general and would tend to justify the violence. Results showed that officers with an inclination to arrest victims in vignette depictions of domestic violence believed that domestic violence is justified in some situations and that women stay in violent relationships for psychological reasons. They also reported less comfort in talking with victims. General sex-role beliefs were unrelated to their responses. Suggestions are made for officer training and further research